Blood pressure response to treatment of obese vs non‐obese adults with sleep apnea. Issue 10 (18th September 2019) - Kuna, Samuel T.; Townsend, Raymond R.; Keenan, Brendan T.; Maislin, David; Gislason, Thorarinn; Benediktsdóttir, Bryndís; Gudmundsdóttir, Sigrun; Arnardóttir, Erna Sif; Sifferman, Andrea; Staley, Beth; Pack, Frances M.; Guo, Xiaofeng; et al.
Abstract: Many patients with obstructive sleep apnea (OSA), but not all, have a reduction in blood pressure (BP) with positive airway pressure (PAP) treatment. Our objective was to determine whether the BP response following PAP treatment is related to obesity. A total of 188 adults with OSA underwent 24‐hour BP monitoring and 24‐hour urinary norepinephrine collection at baseline. Obesity was assessed by waist circumference, body mass index, and abdominal visceral fat volume. Participants adherent to PAP treatment were reassessed after 4 months. Primary outcomes were 24‐hour mean arterial pressure (MAP) and 24‐hour urinary norepinephrine level. Obstructive sleep apnea participants had a significant reduction in 24‐hour MAP following PAP treatment (−1.22 [95% CI: −2.38, −0.06] mm Hg; P  = .039). No significant correlations were present with any of the 3 obesity measures for BP or urinary norepinephrine measures at baseline in all OSA participants or for changes in BP measures in participants adherent to PAP treatment. Changes in BP measures following treatment were not correlated with baseline or change in urinary norepinephrine. Similar results were obtained when BP or urinary norepinephrine measures were compared between participants dichotomized using the sex‐specific median of each obesity measure. Greater reductions in urinary norepinephrine were correlated with higher waist circumference (rho = −0.21, P  = .037), with a greater decrease from baseline in obese compared to non‐obese participants (−6.26 [−8.82, −3.69] vs −2.14 [−4.63, 0.35] ng/mg creatinine; P  = .027). The results indicate that the BP response to PAP treatment in adults with OSA is not related to obesity or urinary norepinephrine levels.